Are some sectors more "youth friendly" than others? Employment regimes, sectors, and gender disparities in the Great Recession. (24th June 2019) - O'Reilly, Jacqueline; Grotti, Raffaele; Russell, Helen
Abstract: Despite national differences in youth employment, many countries share striking similarities in the uneven sectoral distribution of job opportunities for young women and men in Europe. A shift‐share analysis of European Labour Force data identifies "youth‐friendly" sectors, how this varies between countries, and how this changed during the Great Recession. This reveals how youth job opportunities were lost because the sector shrank or because employers were less likely to offer full‐time, permanent contracts. New jobs for youth were more likely to be in part‐time and temporary employment. Youth vulnerability to unemployment is contingent not only on employers' engagement with institutions shaping school‐to‐work transitions but also on gender segregation and to the fact that some sectors have been particularly fragile during the economic crisis. Future research needs to link institutional effects with employers' business strategies to understand how these shape job opportunities for young women and men.